CHANGES HEMODYNAMICS AND SPERMATOGENESIS IN NOT OPERATED MEN OF SUFFERING INGUINAL HERNIA - Chaykovskiy, Yu.B.; Polyvcan, M.I. (World of Medicine and Biology, 2016)
Ultrasonic diagnostic angiography and color laboratory diagnosis of the features of hemodynamics in the testis and semen of men aged 22-35 years in the presence of their oblique inguinal hernia. Established that under these conditions, significantly reduced the maximum and minimum speed as arterial blood flow within the spermatic cord and testicles in the parenchyma decreases its volume. In ejaculate significantly reduced sperm concentration and quantity of the progressive movement. This increases the number of abnormal sperm forms and decreased fertility rate Farris.
Keywords: testicle; hemodynamics; spermatogenesis